Urology mythbusters: do we need to surgically correct vesicoureteral reflux in older girls to prevent problems in future pregnancy? (revision 1). Issue 6 (December 2019) - Acuña, Carolina; López, Pedro-José; Sierralta, María Consuelo; Kurtz, Michael P.; Nelson, Caleb P.; Yankovic, Francisca
Summary: In this edition of Mythbusters we critically examine the premise that, because women with history of vesicoureteric reflux (VUR) are at higher risk of urinary tract infection (UTI) and other morbidity during pregnancy, persistent VUR in older girls should be considered an indication for surgical correction. The literature is very limited in that there are essentially no methodologically robust comparisons of pregnancy outcomes among women whose childhood VUR was or was not surgically repaired. Most of the case series and cohorts find relatively high incidence of UTI and pyelonephritis among pregnant women with a history of VUR, but there is very little to suggest that persistent VUR is itself a risk factor for infection during pregnancy. Indeed, some studies suggest that UTI risk is actually higher among women who previously underwent anti-reflux surgery compared to those who did not, although these data are compromised by significant selection bias. In contrast, there is relatively strong evidence that maternal and fetal morbidity is higher when the mother is known to have renal scarring; such women probably merit close surveillance during pregnancy for infection, hypertension and pre-eclampsia, and other problems. Overall, current evidence is insufficient to support routine anti-reflux surgery in girls with the sole purpose of decreasing complications during future pregnancy, particularly for girls with lower-grades of VUR and no renal scarring. The verdict for this urolegend: it contains a a "teeny, tiny nugget of truth."